Determinasi Faktor Produksi terhadap Produktivitas Padi Sawah di Wilayah Perbatasan: Studi Empiris di Desa Motaulun, Malaka Barat - Klau, Maria Ingria; Koehuan, Jonathan Ebed; Kette, Arlindo U. S.; Suratama, Susana M.; Dethan, Jemmy J. S. (Jurnal Pertanian Terpadu, 2025)
Motaulun Village in West Malaka District is a center of rice paddy production in the Indonesia–Timor-Leste border region. However, rice productivity in this village remains suboptimal despite favorable land and climate potential. This study aims to analyze the influence of production factors such as land area, seed quantity, fertilizer, labor, and farming experience on rice yield. This study employed a quantitative survey of 41 purposively selected rice farmers, with data analyzed using multiple linear regression to assess the effects of land area, seed use, fertilizer, labor, and farming experience on rice production. The results show that land area, seeds, and fertilizer have a positive and significant effect on rice production, while labor and farming experience are not significant. The regression model has a coefficient of determination (R²) of 0.741, indicating that the model can explain 74.1% of the variation in rice production. These findings provide an important empirical basis for agricultural extension agents and policymakers in designing evidence-based strategies to improve agricultural productivity, particularly in rural and border areas with limited resources.